2016
DOI: 10.1007/s00264-016-3285-1
|View full text |Cite
|
Sign up to set email alerts
|

Fracture management in HIV positive individuals: a systematic review

Abstract: Purpose: Human immunodeficiency virus (HIV) infection could potentially play an important role in the management of fractures as they have been shown to affect fracture healing and the post-operative risk of implant sepsis.Methods: A systematic review of the relevant literature was performed on PubMed and Scopus databases. Twenty-six studies were identified, critiqued and analysed accordingly. No randomised controlled trials were identified.Results: HIV positivity was not shown to influence an individual's ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
0
19
1
1
Order By: Relevance
“…There is little evidence surrounding the risk of delayed union and non-union following an open fracture in people with HIV in the current literature but non-union rates of between 10% and 43% have been reported in a small number of studies. 14 Contrary to previous research, this study demonstrated that HIV status does not appear to affect the clinical outcome of fracture healing and may potentially lower the risk of non-union. This could be explained by a number of factors, including direct and indirect immunological effects of HIV on bone, 28,29 and/or characteristics of the study population.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There is little evidence surrounding the risk of delayed union and non-union following an open fracture in people with HIV in the current literature but non-union rates of between 10% and 43% have been reported in a small number of studies. 14 Contrary to previous research, this study demonstrated that HIV status does not appear to affect the clinical outcome of fracture healing and may potentially lower the risk of non-union. This could be explained by a number of factors, including direct and indirect immunological effects of HIV on bone, 28,29 and/or characteristics of the study population.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies had suggested non-union in 0-11% of fractures in HIV-positive individuals following surgical fixation of a fracture. 14 Antiretroviral therapy regimen, CD4 count, and viral load at baseline were also not associated with a significant risk of delayed union in the study population of participants with HIV. However, a greater number of ART naïve participants and more of those with a higher viral load developed delayed union and a much larger, appropriately powered, study is required to investigate this further.…”
Section: Discussionmentioning
confidence: 80%
“…In a review of twenty-six patients, Wijesekera and colleagues suggested in open fractures managed with internal fixation, postoperative wound infection rates were significantly increased in HIV-positive population compared to HIV-negative controls. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Routine tests reveal anemia, hypoproteinemia, and comorbidities. Serological marker testing for hepatitis B surface antigen,9 HIV,10 and hepatitis C11 is mandatory. Multiple transfusions and surgeries make these patients susceptible for viral infections.…”
Section: Introductionmentioning
confidence: 99%